Effects of midazolam supplementation on ketamine anaesthesia in butorphanol-xylazine premedicated horses - MALIK, V; SINGH, B (The Indian Journal of Animal Sciences, 2011)
Clinically healthy horses (6) were utilized to evaluate the effect of midazolam supplementation on ketamine anaesthesia in horses premedicated with butorphanol and xylazine. Midazolam supplementation resulted in to slight increase in duration of anaesthesia and a significant improvement in the quality of analgesia, muscular relaxation and depth of anaesthesia with out producing any adverse effect on cardiorespiratory system. Â